Outcomes of elective surgery undertaken in independent sector treatment centres and NHS providers in England: audit of patient outcomes in surgery. (19th October 2011) - Chard, J; Kuczawski, M; Black, N; van der Meulen, J
Abstract : Objective To compare characteristics of patients and outcomes after elective surgery in independent sector treatment centres (ISTCs) and NHS providers. Design Follow-up study with outcomes reported by patients three to six months after surgery. Setting 25 ISTCs and 72 NHS providers in England. Population Consecutive patients undergoing hip or knee replacement (5671 in ISTCs and 14 292 in NHS), inguinal hernia repair (640 and 2023, respectively), or surgery for varicose veins (248 and 1336, respectively). Main outcomes Symptoms and disability reported by patients (Oxford hip and knee scores on a 48 point scale; Aberdeen varicose vein questionnaire) and quality of life (EuroQol EQ-5D score). Results Patients in ISTCs were healthier than those in NHS providers, had less severe preoperative symptoms, and were more affluent, though the differences were small. With adjustment, patients undergoing joint replacements in NHS providers had poorer outcomes: difference of −1.7 (95% confidence interval −2.5 to −0.9) on the Oxford hip score and −0.9 (−1.6 to −0.2) on the Oxford knee score. They more often reported complications: odds ratio 1.3 (95% confidence interval 1.1 to 1.5) for hip and 1.4 (1.2 to 1.6) for knee. There were no significant differences in outcomes after surgery for hernia or varicose veins, except that NHS patients more often reported poor results after hernia repair (1.4, 1.0 to 1.9) and additional surgery after varicose vein surgery (2.8, 1.2 to 6.8). Conclusion Patients undergoing surgery in ISTCs were slightly healthier and had less severe conditions than those undergoing surgery in NHS providers. Some outcomes were better in ISTCs, but differences were small compared with the impact ISTCs could have on the provision of elective services.